CORRELATION OF MIDWIFEâS COOPERATION, MOTIVATION, ATTITUDE AND PERFORMANCE ON ANTENATAL CARE - Djunawan, Achmad; Haksama, Setya (Jurnal Administrasi Kesehatan Indonesia, 2015)
ABSTRACTAntenatal care in last three years at Kecamatan Kejayan did not reach the target, 100% for K1 and 95% for K4. This research aims to analyze the correlation of midwifeâs cooperation, motivation, attitude, and performance on antenatal care in non insurance and insurance patients group. This is a quantitative research with cross sectional design. Spearman Correlation and Coeficient Contingency were used in this research to analyze the data. 36 midwifes were interviewed to obtain data.The results show that majority midwifes has cooperation with primary health care. Midwifeâs motivation was high and attitude was positive. Midwifeâs performance to non insurance and insurance patients was very high. There was moderate correlation (r=0,446) between cooperation (midwife with primary health care) and the performance to non insurance patients. There was very weak correlation (r=0,111) between cooperation (mindwife with doctor) and performance to insurance patients, and weak correlation (r=0,311) to non insurance patients. There was weak correlation (r=0,086) between motivation and performance to insurance patients, whereas correlation to non insurance was moderate (r=0,521). There was strong correlation (r=0,707) between attitude and performance to non insurance patient. The conclusion, attitude has most significant with performance in non insurance patient group.Â Keywords: antenatal care, attitude, cooperation, motivation, performance